2022
DOI: 10.1111/obr.13489
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and the risk for metabolic syndrome among healthcare workers: A systematic review and meta‐analysis

Abstract: Summary Shift work, defined as work occurring outside typical daytime working hours, is associated with an increased risk for metabolic syndrome (MetS) due to several biological and environmental changes. The MetS refers to the clustering of several known cardiovascular risk factors, including insulin resistance, obesity, dyslipidemia, and hypertension. This systematic review aims to evaluate the literature on the association between shift work and the risk of MetS in employees of the health sector. A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 97 publications
2
35
0
Order By: Relevance
“…Anthropometric measurements such as weight, height, and waist and hip circumference were measured using standard equipment. Details of anthropometric measurements are described elsewhere 16 . The blood pressure was measured on two occasions while seated following at least a 10-minute rest using a digital blood pressure monitor (Omron Healthcare, Singapore).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropometric measurements such as weight, height, and waist and hip circumference were measured using standard equipment. Details of anthropometric measurements are described elsewhere 16 . The blood pressure was measured on two occasions while seated following at least a 10-minute rest using a digital blood pressure monitor (Omron Healthcare, Singapore).…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study was conducted among health care workers in Nawaloka Hospital, Colombo, Sri Lanka, between July and August 2021. The details of the study have been discussed elsewhere 16 . Male and female shift employees were chosen using a stratified sampling procedure after being matched for age.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately, 18% of all European workers work in shifts, and this rate is as high as 35% in some countries [1]. This type of work schedule alters circadian rhythms of the workers which may adversely affect glucose and lipid metabolism, inflammatory process, and nervous system, and also increase the risk of atherosclerosis, dyslipidemia, and insulin resistance [2,3]. In recent years, numerous studies [4][5][6][7][8][9] have been done about the relationship between cardiometabolic diseases such as cardiovascular disease, type 2 diabetes [4,5] and obesity [6,7] with shift work.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effect of shift work on the cardiovascular diseases risk factors help us control these diseases. Although the results of various studies have shown that shift work contributes to the development of the cardiovascular disease [2][3][4][5]. There are few studies on the effect of shift work on the risk factors which cause this relationship [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…5 Shiftwork, which often involves work outside the conventional daytime, is a well-known risk factor for developing chronic diseases such as cardiovascular, obesity, metabolic syndrome (MetS), and type 2 diabetes mellitus. 6,7 The BF distribution is important in assessing the risk of cardiometabolic health, obesity, and other obesity-associated disorders. 8 A recent study found that night shiftworkers had a higher BF percentage (BF%) than regular day workers in the same body mass index (BMI) range.…”
mentioning
confidence: 99%